Absorption and water movement resistance in cacao - de Amorim, Solange Maria Costa; Valle, Raul rné (Pesquisa Agropecuaria Brasileira, 1993)
The effects of root temperature on water movement resistance were studied on ca-cao (Theobroma cacao L.) seedlings under greenhouse conditions at root temperatures of 10°, 20°, 30° and 40°, on leaves covered with aluminum foil and black plastic bags and on uncovered leaves. The leaves were located at base, at the intermediate part and at the apex of the stem. Measurements of water potential and its components, transpiration, photosynthesis, temperature, and stomatic conductance were done by psychrometry in the uncovered leaves adjacent to the covered ones. The results suggest that the resistance to water movement does not depend on the position of the leaves in the stem, but depends on the transpirational flux, and that the water potential gradients across the plant vary at temperatures greater than 30°C. Gas exchanges at different root temperatures depend on the water status of the plant.